Should competencies be broadly shared in new ventures' founding teams?. (23rd September 2020) - Reese, Daniel; Rieger, Verena; Engelen, Andreas
Abstract: Research Summary: Building on human capital theory, this study establishes the concept of the "sharedness" of competencies in founding teams. Based on prominent entrepreneurship research, we differentiate among entrepreneurial, managerial, and technical competencies. We test our model with 1, 863 founding teams of US‐based new ventures by means of a multisource dataset that uses the LinkedIn skills and endorsements sections to measure competencies in a novel way. The results suggest that strong sharedness of entrepreneurial competencies is positively related to new ventures' performance, while sharedness of managerial skills is negatively related to performance. These results have theoretical implications for human capital and entrepreneurship research and practical implications for investors and founders. Managerial Summary: It is common wisdom in entrepreneurial practice that different types of competencies are required in founding teams. Our research adds to this notion that it does not only matter that different competencies are represented, but also how these competencies are represented. First, all members should have some entrepreneurial competencies, as mastering the challenges related to opportunity recognition is the major task a new venture has to address, and synergies are central to success in this regard. Second, deep expertise in managerial competencies in one or a few individuals with specialized knowledge, such as project management and managing customer relationships, is beneficial to new ventures' funding success. These findings provide important implications for founding team composition.